Beyond the parish pump: what next for public health? - Alex Hall; Jonathan Hammond; Donna Bramwell; Anna Coleman; Lynsey Warwick-Giles; Kath Checkland (BMC, 2018)
Abstract Background Public health has had a history characterised by uncertainty of purpose, locus of control, and workforce identity. In many health systems, the public health function is fragmented, isolated and under-resourced. We use the most recent major reforms to the English National Health Service and local government, the Health and Social Care Act 2012 (HSCA12), as a lens through which to explore the changing nature of public health professionalism. Methods This paper is based upon a 3-year longitudinal study into the impacts of the HSCA12 upon the commissioning system in England, in which we conducted 141 interviews with 118 commissioners and senior staff from a variety of health service commissioner and provider organisations, local government, and the third sector. For the present paper, we developed a subset of data relevant to public health, and analysed it using a framework derived from the literature on public health professionalism, exploring themes identified from relevant policy documents and research. Results The move of public health responsibilities into local government introduced an element of politicisation which challenged public health professional autonomy. There were mixed feelings about the status of public health as a specialist profession. The creation of a national public health organisation helped raise the profile of profession, but there were concerns about clarity of responsibilities, accountability, and upholding 'pure' public health professional values. There was confusion about the remit of other organisations in relation to public health. Conclusions Where public health professionals sit in a health system in absolute terms is less important than their ability to develop relationships, negotiate their roles, and provide expert public health influence across that system. A conflation between 'population health' and 'public health' fosters unrealistic expectations of the profession. Public health may be best placed to provide leadership for other stakeholders and professional groups working towards improving health outcomes of their defined populations, but there remains a need to clarify the role(s) that public health as a specialist profession has to play in helping to fulfil population health goals.